Manganese molybdate and its Fe-substituted products as new efficient electrocatalysts for oxygen evolution in alkaline solutions - Srirapu V.K.V.P.; Kumar M.; Awasthi R.; Singh R.N.; Sinha A.S.K. (My University, 2025)
Pure and Fe-substituted manganese molybdates with nominal compositional formula FexMn1-xMoO4 (x = 0, 0.25, 0.50 and 0.75) have been prepared by a co-precipitation method at pH ≈ 2 and characterized by FT-IR, XRD, XPS, TEM, electrochemical impedance and polarization techniques. The oxygen evolution reaction (OER) study reveals that Fe substitutions from 0.25 to 0.75 mol for Mn increase the apparent electrocatalytic activity of the base oxide showing maximum with 0.5 mol Fe. At E = 0.60 V vs. Hg/HgO in 1 M KOH at 298 K, the apparent activity of the base oxide increased ∼58 times. It is observed that on Fe addition, the Tafel slope decreases from ∼60 to ∼35 mV, however, the order of the OER with respect to OH- concentration as observed ∼2 on the base oxide (i.e. MnMoO4) does not change. Copyright © 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.